2021
DOI: 10.1101/2021.05.18.21257396
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Phenome-Wide Association Study of genes associated with COVID-19 severity reveals shared genetics with complex diseases in the Million Veteran Program

Abstract: Background There are certain pre-existing conditions which leads in increased risk of coronavirus disease 2019 (COVID-19) severity and mortality. The objective of this study is to determine shared genetic architecture between COVID-19 severity and other medical conditions using electronic health record (EHR) data from diverse patient populations. Methods and Findings: We conducted Phenome-wide association study (PheWAS) of genetic variants associated with severe COVID-19 in two biobanks with EHR and genomic da… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 39 publications
(69 reference statements)
3
12
1
Order By: Relevance
“…The copyright holder for this preprint this version posted November 7, 2022. ; https://doi.org/10.1101/2022.11.03.22281867 doi: medRxiv preprint and immunodeficiency, as well as autoimmune diseases including SLE. These results support the previous studies suggesting that TYK2 has opposing associations with COVID-19 susceptibility and predisposition to autoimmune conditions 32,36 . Notably, the results of all geneset enrichment and pathway analyses are indicative of a role for COVID-19-associated genes in essential immune processes, thereby emphasizing the likely importance of underlying genetic variation on the impaired host immune response to COVID-19 1,3 .…”
Section: (Which Was Not Certified By Peer Review)supporting
confidence: 92%
See 1 more Smart Citation
“…The copyright holder for this preprint this version posted November 7, 2022. ; https://doi.org/10.1101/2022.11.03.22281867 doi: medRxiv preprint and immunodeficiency, as well as autoimmune diseases including SLE. These results support the previous studies suggesting that TYK2 has opposing associations with COVID-19 susceptibility and predisposition to autoimmune conditions 32,36 . Notably, the results of all geneset enrichment and pathway analyses are indicative of a role for COVID-19-associated genes in essential immune processes, thereby emphasizing the likely importance of underlying genetic variation on the impaired host immune response to COVID-19 1,3 .…”
Section: (Which Was Not Certified By Peer Review)supporting
confidence: 92%
“…The other significant finding from PheWAS in the HA cohort was the association of rs35705950 in the proximity of MUC5B with alveolar or parietoalveolar pneumonitis. Our findings support the results of previous studies that showed the rs35705950-T allele being associated with idiopathic pulmonary fibrosis while being a protective variant for COVID-19 32 . Finally, PheWAS in the HA cohort also revealed an association of the rs12979860-T allele in IFNL4 with viral hepatitis and cirrhosis.…”
Section: Phewas In the Mount Sinai Biome Biobanksupporting
confidence: 92%
“…A noteworthy study by Anurag Verma and Matteo D'Antonio showed that rs2277732 was associated with hospitalization and severity of COVID-19, respectively (19,20), whilst the results of the present study similarly found that rs2277732 was associated with both hospitalization and severity of COVID-19 and CVD death, but there exist no studies involving the association of rs2277732 with CVD death. These results suggest that the above-mentioned COVID-19-related SNPs may indirectly increase CVD death through other factors such as blood type, but this is only an inference and needs to be verified by further studies.…”
Section: Discussioncontrasting
confidence: 48%
“…The results of Anurag Verma et al showed that the rs505922 SNP in the ABO blood group gene was significantly associated with COVID-19 severity and hospitalization ( 17 ). Similarly, our findings found an association between both COVID-19 severity and hospitalization and CVD death, with rs505922.…”
Section: Discussionmentioning
confidence: 99%
“…Ptpn1 then dephosphorylates the TYK2 protein thereby impeding TYK2-mediated T helper-1 (Th1) differentiation and interferon signaling essential for innate and acquired immune responses to viruses. Recently, a TYK2 missense mutation has been reported to confer high risk for COVID-19 severity ( 32 ). Consequently, androgen suppression of TYK2 signaling in T lymphocytes may be an important determinant of COVID-19 outcome.…”
Section: Discussionmentioning
confidence: 99%